Gamma tocopherol effect on LPS-induced sputum neutrophilia is not modified by BMI or GSTM1 genotype - Sood, Amika K. (J Allergy Clin Immunol, 2019)
Gamma tocopherol may be beneficial as a primary or complementary therapeutic agent in conditions with neutrophilic airway inflammation. Its effects are not modified by BMI or GSTM1 genotype, allowing for its use in a broader population.